Ginger Milk: Innovation in Pure Milk Processing in Improving the Economy of Dairy Farmers - Alifa Setyaningrum, Krista; Fathi Alfalah, Muhammad; Fatullatifah, Lut; Kusnawan, Wawan (CV. BImbingan Belajar Assyfa, 2023)
Wagir Kidul Village, Pulung District, Ponorogo Regency, is the 2nd largest milk-producing village in Ponorogo. In this case, group 2 of the KKN Muhammadiyah University of Ponorogo has the opportunity to serve and work in the community by creating an innovation work program for processing superior village products. In this case, we have an idea to help improve the people's economy in the village by making innovations in processing pure cow's milk. We mix pure cow's milk with ginger and other flavors. The method used in this research is community education and training. This innovation produces results where processed milk has a higher nutritional content than pure milk. Apart from that, the selling value of processed milk has increased more than that of pure milk's, where profits have increased by almost 20%. Based on this, it can be seen that the innovation of processing pure cow's milk into Ginger Milk has positively impacted the community's economy, especially for cattle breeders in Wagir Kidul village, Pulung District, Ponorogo Regency.